MODEL PENGEMBANGAN ASUHAN KEPERAWATAN PADA RESPON HOSPITALISASI ANAK TODLER DENGAN KUANTITAS DANKUALITAS TIDUR DI RUMAH SAKIT KARTINIKABUPATEN MOJOKERTO - Ratnaningsih, Tri; Wahyuni, Lutfi (JURNAL KEPERAWATAN BINA SEHAT, 2013)
Children were first treated, never had an idea of being treated in hospital, the environment changes, the staff were very unfamiliar, stressful in itself for children (Perry & Potter, 2005). This research aims to develop a model of Nursing Response Toddlers with Children Hospitalization Quantity Quality in Hospital Kartini Mojokerto. Observational design (survey), conducted cross-sectional, population of children 1-3 years old. Respondents children 13-24 months 17 children (56.7%). Respondents were given a nursing response after mild hospitalisasinya 19 children (63.3%). Respondents after being given the quality of nursing care are met her 16 children (53.3%). Mann Whitney test standard error of 0.05 (5%) probability value of 0.000 <0.05, there is a response effect of hospitalization on sleep quantity of children 1-3 years old. Children meet quality sleep when someone does not show signs of lack of sleep, not having problems sleeping.Keywords: Hospitalization, sleep quality, sleep quantity